Asymptotics of approximation of ψ-differentiable functions of many variables - Lasuriya, R. A. (Ukrains’kyi Matematychnyi Zhurnal, 2008)
We investigate approximative characteristics of classes of ψ-differentiable multivariable functions introduced by A. I. Stepanets. We give asymptotics of the approximation of functions from these classes.